2017
DOI: 10.1080/15376516.2017.1337259
|View full text |Cite
|
Sign up to set email alerts
|

2,3′,4,4′,5-Pentachlorobiphenyl impairs insulin-induced NO production partly through excessive ROS production in endothelial cells

Abstract: Polychlorinated biphenyls (PCBs) have been reported to be associated with increased risk to hypertension, atherosclerosis, cardiovascular disease, etc. 2,3',4,4',5-Pentachlorobiphenyl, known as PCB-118, is a member of coplanar PCBs which renders their structure similar to polychlorinated dibenzo-p-dioxins (PCDDs) and has dioxin-like activity. In our current study, we investigated the effect of PCB-118 exposure on nitric oxide (NO) production and the underlying mechanisms in vitro. Exposure of PCB-118 impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Second, several experimental studies have shown that PCBs increased reactive oxygen species and oxidative stress. 48 51 52 53 Similar findings have also been reported by us in humans. 54 In that study, PCBs and OC pesticides were related to circulating levels of oxidized LDL and conjugated diens.…”
Section: Mechanisms Whereby Lipid-soluble Pop Could Affect Atherosclesupporting
confidence: 90%
See 1 more Smart Citation
“…Second, several experimental studies have shown that PCBs increased reactive oxygen species and oxidative stress. 48 51 52 53 Similar findings have also been reported by us in humans. 54 In that study, PCBs and OC pesticides were related to circulating levels of oxidized LDL and conjugated diens.…”
Section: Mechanisms Whereby Lipid-soluble Pop Could Affect Atherosclesupporting
confidence: 90%
“…Exposure of human umbilical vein endothelial cells (HUVECs) to PCB-118 attenuated insulin-induced NO production and activity of endothelial NO synthase. 51 Furthermore, PCB104 exposure of ex vivo rat aortic attenuated acetylcholine-mediated vasodilation, an NO-dependent process. 55 Fourth, apoptosis of endothelial cells is one mechanism in atherosclerosis formation.…”
Section: Mechanisms Whereby Lipid-soluble Pop Could Affect Atherosclementioning
confidence: 97%
“…β-blockers, thiazide diuretics and neuroleptic drugs). Several downstream effects of the agonistic/antagonistic actions on the receptors described above, such as mitochondrial dysfunction [ 38 ], inflammation [ 39 ], oxidative stress [ 40 ] and alterations in thyroid and cortisol pathways [ 41 ], comprise possible mediating pathways linking different EDCs to glucose disturbances.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Oxidative stress is one of the critical pathological mechanisms of ischemic stroke (Jena et al., 2017 ). Excessive ROS are mainly derived from mitochondria with a functional disorder, causing peroxidative damage of nucleic acids, lipids and proteins, and impairing normal physiological functions (Yang, Can, et al., 2017 ). Excessive ROS production promotes pathological processes of neurodegenerative diseases (Zhao et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%